The development of Kolb Learning Style and 4c's 21st century skill integration e-book in Pedagogy Subject - Santika, Tiara; Ganefri, Ganefri; Jalinus, Nizwardi; Syahril, Syahril; Rizal, Fahmi; Sukardi, Sukardi; Rispendra, Rispendra; Nabawi, Rahmat Azis (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This research was based on the demands of the 21st century in which teachers should have 4 skills (critical thinking, creativity, collaboration, and communication). Teachers are required to change the way of teaching that initially (teacher-centered) turns into (student-centered) and able to participate to follow the development of technology. Therefore, E-book learning is needed that can present material pedagogy integrated with kolb learning and 4C's. This research aims to produce the final product in the form of valid e-book media learning, practical and effective in pedagogy subject. This was a research and development (Research and Development) research. This development research used ADDIE development model consisting of 5 stages which were Analysis, Design, Development, Implementation and Evaluation). Based on the results, e-book validation testing conducted by three validators, it obtained Aiken's score 0.9 with a valid category. The test results practicalities of the teachers and the students were 86% in the practical category. The effectiveness test results was 89.65%. Thus, it can be concluded that this research has produced a pedagogical e-book which is valid, practical and effective.